2009
DOI: 10.1177/0269215509338999
|View full text |Cite
|
Sign up to set email alerts
|

Promoting the use of outcome measures by an educational programme for physiotherapists in stroke rehabilitation: a pilot randomized controlled trial

Abstract: In this pilot trial it was not proven that tutor expertise in stroke care influences the actual use of outcome measures, but it warrants a future study with sufficient power to investigate the influence of the tutor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 25 publications
0
30
0
1
Order By: Relevance
“…Two of the studies were in an outpatient pediatric setting (28,34). Seven of the studies targeted physiotherapists only (1,28,29,31,(33)(34)(35) , one study occurred with community mental health professions (unspecified but occupational therapy assumed) (25), one study each targeted occupational therapists only (30) and prosthetists only (27), and one study involved physiotherapists, occupational therapists and speech-language pathologists (32). While nine studies reported various provider characteristics such as age, gender, years of experience, work location, and caseload levels, one study reported only the professional discipline of the providers (33), and one study reported only 'mental health providers' without specifying any further provider characteristics (25).…”
Section: Study Descriptorsmentioning
confidence: 99%
See 4 more Smart Citations
“…Two of the studies were in an outpatient pediatric setting (28,34). Seven of the studies targeted physiotherapists only (1,28,29,31,(33)(34)(35) , one study occurred with community mental health professions (unspecified but occupational therapy assumed) (25), one study each targeted occupational therapists only (30) and prosthetists only (27), and one study involved physiotherapists, occupational therapists and speech-language pathologists (32). While nine studies reported various provider characteristics such as age, gender, years of experience, work location, and caseload levels, one study reported only the professional discipline of the providers (33), and one study reported only 'mental health providers' without specifying any further provider characteristics (25).…”
Section: Study Descriptorsmentioning
confidence: 99%
“…Nine of the eleven studies had an overall quality rating of weak. Two studies had an overall rating of moderate (31,35). Only one of the studies had strong ratings for any of the six components that made up the overall quality rating (31).…”
Section: Study Qualitymentioning
confidence: 99%
See 3 more Smart Citations